Child labor : the role of income variability and access to credit in a cross-section of countries - Dehejia, Rajeev H. 1997- (Policy research working paper, 2002)
In the absence of developed financial markets, households appear to resort to child labor to cope with income variability. This evidence suggest that policies aimed at increasing households' access to credit could be effective in reducing child labor